Can Local Ordinances Prevent Neighborhood Destabilization?. Issue 3 (3rd May 2016) - Fitzpatrick, Thomas J.; Nelson, Lisa; Richter, Francisca G.-C.; Whitaker, Stephan
Abstract: This article assesses the ability of local housing ordinances to prevent neighborhood destabilization, specifically that arising as a consequence of the most recent housing crisis. We evaluate the degree to which vacancy registrations and point-of-sale inspection requirements influenced housing market outcomes during the housing crisis. With comprehensive real property data from Cuyahoga County, Ohio, we measure outcomes that characterize housing market distress including foreclosures, sales below the tax-assessed value, bulk sales, flipping, and property tax delinquency. We evaluate outcomes across properties in regulated and unregulated municipalities using matching procedures on linked data containing property, neighborhood, loan, and transaction characteristics. We find evidence that vacancy registrations substantially reduce foreclosures. In contrast, we find little evidence that point-of-sale inspections reduce undesirable transactions. Rather, properties in cities with inspection requirements displayed higher levels of foreclosure and tax delinquency relative to the control group during the study period.